Good for construction drawing of M&E punches and openings in basement of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding good for construction drawing of M&E punches and openings in basement of BRAC University new campus project.